Intercalibration of counting methods for Ostreopsis spp. blooms in the Mediterranean Sea - Vassalli, Massimo (2018)
This paper describes the adoption and validation of two innovative methods for the automated count of Ostreopsis spp. concentration in sea water: a molecular assay based on RT-qPCR and an opto-electronic device implementing automatic recognition algorithms. The proposed approaches were tested on samples coming from different locations along the Mediterranean Sea and compared with the standard counting method based on microscopy observation by a taxonomy expert. The results demonstrate the effectiveness of both automatic approaches which provide a valuable tool, mostly cost and time effective, for the establishment of wide pan-Mediterranean monitoring strategies of Ostreopsis spp. blooms. Moreover, the two automatic methods demonstrated the ability to discriminate for the presence of a different but similar species, O. fattorussoi, for which new species-specific qPCR primers were developed.